Relative intensities and compositions of multifactorial peak kinematic and mechanical demands in elite youth soccer - Yousefian, Farzad; Zafar, Abdullah; Nakamura, Fábio Y.; Menezes, Pedro; Brito, João; Travassos, Bruno (Frontiers in Sports and Active Living, 2025)
BackgroundCharacterizing the most demanding passages (MDP) of physical activity during soccer competition is essential for optimizing training prescription and player monitoring. However, research investigating kinematic and mechanical MDP using a multifactorial criterion variable approach in elite youth soccer players remains limited. This study examined the relative intensities and compositional structure of multifactorial kinematic and mechanical MDP across different durations in an elite youth international tournament.MethodsLocomotor activity data were collected from 17 elite youth players across five matches of an international tournament using GPS technology. Kinematic and mechanical MDP were identified using multifactorial criterion variables: MDPk (kinematic) and MDPm (mechanical). Linear mixed models assessed relative intensities (m·min−1 or efforts·min−1) and the univariate constituent compositions of MDPk [moderate-speed running [MSR], high-speed running [HSR], sprinting [SPR]] and MDPm [high-intensity accelerations [ACC3], decelerations [DEC3]] across rolling (R’) 1-, 3-, and 5-minute durations, comparing matches and positional groups (central, lateral).ResultsDifferences between matches and positions were observed only for R1’ MDPk intensities. Both MDPk and MDPm intensities decreased as duration increased. Between-match differences were observed for MDPk composition, particularly for %HSR and %SPR. MDPk composition was duration-dependent, as %HSR and %SPR were greater in R1’ than R3’ and R5’, while %MSR followed the opposite trend. In contrast, MDPm composition remained stable across durations.ConclusionsPractitioners should consider both the relative intensities and compositional structures of MDPk and MDPm when evaluating multifactorial peak demands in soccer. Analyzing kinematic and mechanical MDP as multifactorial constructs offers critical insights into the contribution of specific locomotor demands across various durations. This approach emphasizes the importance of duration-specific analyses in optimizing training, recovery, and match preparation strategies, thereby facilitating targeted training interventions and enhancing player readiness for competition.